El juego: una estrategia lúdico-pedagógica para el fortalecimiento de las relaciones socio afectivas en los estudiantes de tercer grado de básica primaria (2024)
The general objective of this study was to strengthen the socio-affective relationships of 3°C students of the El Pueblo district educational institution through the implementation of recreational-pedagogical strategies in the city of Barranquilla. Methodologically, it was designed under a qualitative approach, since the behavior of the students will be observed naturally within their context, which in turn will allow them to develop and see their scenario, the people and the groups as a whole. People are studied in their current contexts, in the case of this project in the context in which the students find themselves, in this way they will be able to articulate with each of them, becoming sensitive to the affects that will be produced. The results obtained from the students show that their socio-affective relationships are shy when it comes to expressing their opinions. which may be related to difficulty establishing social relationships with others and lack of social skills, which indicates that it must continue to be strengthened through the playful-pedagogical strategies that were implemented, which allowed improving socio-affective relationships in the classroom of the students. students, research actors, who will allow them to advance within their personal and comprehensive development. Thus, it is concluded that effective social relationships generate better performance within the processes they carry out, for each of the students, therefore, it is pertinent to strengthen them throughout the school process.